Stick-Slip Behaviour of a Viscoelastic Flat Sliding along a Rigid Indenter - Budi Setiyana (Japanese Society of Tribologists, 2016)
The sliding contact of soft material surface due to a rigid indenter is different from metal and some other polymers. A stick-slip motion is more frequently obtained than a smooth motion. By modeling the soft material as low damping viscoelastic material, this study proposes an analytical model to identify the stick-slip behavior of sliding system. The sliding system is a fixed rigid indenter that slides against on a moving soft material surface. A stick-slip model is developed and the motion of the sliding system is assumed to be in a solely tangential direction. By implementing the simple coulomb friction law, an exact solution is presented in the case of no damping of the sliding system. Results show that the periodic displacement of the stick-slip model is strongly depending on the friction force, sliding velocity and material stiffness. Furthermore, the effect of a viscous damping and velocity-dependent friction on the behaviour of the sliding system are discussed.